LiCl‐induced immunomodulatory periodontal regeneration via the activation of the Wnt/β‐catenin signaling pathway. (8th June 2022) - Zheng, Xiumei; Wang, Shengfang; Xiao, Lan; Han, Pingping; Xie, Kunke; Ivanovski, Saso; Xiao, Yin; Zhou, Yinghong
Abstract: Background: Growing evidence suggests that excessive inflammation hampers the regenerative capacity of periodontal ligament cells (PDLCs) and that activation of the Wnt/β‐catenin pathway is crucial in suppressing immune dysregulation. Objective: This study aimed to establish the role of the Wnt/β‐catenin in regulating the immune microenvironment and its subsequent impact on periodontal regeneration. Methods: Lithium chloride (LiCl, Wnt activator) was administered daily into the standard periodontal defects created in 12‐week‐old Lewis rats. Harvested at 1‐week and 2‐week post‐surgery, samples were then subjected to histological and immunohistochemical evaluation of macrophage distribution and phenotype (pro‐inflammatory M1 and anti‐inflammatory M2). A murine macrophage cell line, RAW 264.7, was stimulated with LiCl to activate Wnt/β‐catenin. Following treatment with the conditioned medium derived from the LiCl‐activated macrophages, the expression of bone‐ and cementum‐related markers of the PDLCs was determined. The involvement of Wnt/β‐catenin in the immunoregulation and autophagic activity was further investigated with the addition of cardamonin, a commercially available Wnt inhibitor. Results: A significantly increased number of macrophages were detected around the defects during early healing upon receiving the Wnt/β‐catenin signaling cue. The defect sites in week 2 exhibited fewer M1 and more M2 macrophages along with an enhanced regeneration of alveolar bone and cementum in the Wnt/β‐catenin activation group. LiCl‐induced immunomodulatory effect was accompanied with the activation Wnt/β‐catenin signaling, which was suppressed in the presence of Wnt inhibitor. Exposure to LiCl could induce autophagy in a dose‐dependent manner, thus maintaining macrophages in a regulatory state. The expression level of bone‐ and cementum‐related markers was significantly elevated in PDLCs stimulated with LiCl‐activated macrophages. Conclusion: The application of Wnt activator LiCl facilitates the recruitment of macrophages to defect sites and regulates their phenotypic switching in favor of periodontal regeneration. Suppression of Wnt/β‐catenin pathway could attenuate the LiCl‐induced immunomodulatory effect. Taken together, the Wnt/β‐catenin pathway may be targeted for therapeutic interventions in periodontal diseases.